Hubungan Pengetahuan dan Sikap dengan Praktik Konsumsi Mie Instan pada Konsumen Warmindo K17 di Surabaya - Rr. Revana Janys Nadyna; Rahayu Dewi Soeyono (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Instant noodles are a widely consumed fast food product, and consumer understanding of their nutritional content and potential health risks is thought to influence both attitudes and behaviors related to their consumption. Specifically, this understanding may affect how individuals meet their energy requirements—measured by the Recommended Energy Intake (REI)—through the consumption of instant noodles. This study aims to examine the relationship between knowledge and attitudes and the consumption practices of instant noodles among consumers at Warmindo K17 in Surabaya. A quantitative, cross-sectional research design was employed. Data were collected using a structured questionnaire distributed to 100 respondents selected through simple random sampling. Descriptive statistics, Spearman’s rank correlation, and Fisher’s exact tests were utilized to analyze the relationships between knowledge, attitudes, and consumption practices. The results indicated a statistically significant association between knowledge levels and consumption practices (p = 0.030), as well as between attitudes and consumption practices (p = 0.006), with both p-values falling below the 0.05 threshold. These findings suggest that higher levels of nutritional knowledge and more positive attitudes are associated with healthier instant noodle consumption practices. The study underscores the importance of enhancing public nutrition education to encourage healthier dietary behaviors. Furthermore, the findings may offer valuable insights for Warmindo business operators in developing more effective strategies for communicating product information to consumers.